Diferentes abordagens no desenvolvimento de uma sequência de ensino CTSA/QSC sobre aquecimento global por três professores em escolas públicas de Minas Gerais - Tarcisio da Eucaristia Tadeu de Mello (2016)
This research aims to determine how a teaching sequence on global warming and climate change was worked by three Physics teachers into three public schools. The theme involves a controversial and interdisciplinary subject and the sequence promotes the discussion and study of the debate between two opposing groups: one defending the thesis that global warming and climate change are produced by human activity, anthropogenic causes, the other claims the warming and climate changes being a consequence of natural causes. The issue presents an interdisciplinary dimension, and even potential of cross exploration, the teaching sequence Physics concerns a STSE approach by means of socio scientific issues (SSI). Using as source of information the speech of teachers in interviews, we seek to identify what were their choices in the exploration of STSE/SSI assumptions presented by the teaching sequence.